Examination of optimal performance mood status in sedentary women according to certain variables - Orhan Ahmet Şener; Osman İmamoğlu (ROL Spor Bilimleri Dergisi)
This study investigates the Optimal Performance Mood State in sedentary women according to their behavioral change stages, perception of their health and appearance, and menstrual status. 774 sedentary women participated in the study. One-way analysis of variance was performed in statistical procedures. According to the behavioral change stages, a statistically significant change was found in the dimensions of task difficulty, awareness in action, clear goals, secondary notification, focus on the task, sense of control, transformation of time and experience of achieving the goal, and decrease in awareness subscales in optimal performance emotional state (p<0.001). When comparing the optimal performance mood and sub-dimension averages of sedentary women according to the “your health” variable, a statistically significant difference was found in all dimensions (p<0.05 and p<0.001). When comparing the optimal performance mood and sub-dimension averages of sedentary women according to the variable of your physical image relative to yourself, a statistically significant difference was found in all dimensions except decreased awareness (p<0.001). Conclusion: It was concluded that Optimal Performance Mood in sedentary women varies according to the stages of behavioral change and their perception of their health and appearance. As the exercise status of sedentary women increases, their optimal performance mood improves positively as they perceive their health as good and accept their appearance as good. Women should be encouraged to do sports regularly to improve their optimal performance mood, receive psychological support to perceive their health as good and encourage their desire to look beautiful. It may also be recommended that women receive support for regular menstruation to increase their optimal performance mood.